Addressing anti-Black racism within public health in North America: a scoping review - Lucina Rakotovao; Michelle Simeoni; Caroline Bennett-AbuAyyash; Taheera Walji; Samiya Abdi (BMC, 2024)
Abstract Objectives The syndemic that is COVID-19 and the disproportionate policing of Black communities have recently generated mass social consciousness of the anti-Black racism (ABR) pervading health, social, and cultural institutions. However, little is known about the implementation of public health measures addressing ABR in an evolving pandemic context. The objective of this scoping review is to provide an overview of public health initiatives undertaken to address ABR across North American jurisdictions between December 2019 and June 2022. Methods A search for public health initiatives was conducted in June 2021 across MEDLINE, Ovid Embase, EBSChost, CINAHL, SocINDEX, and Google.ca. Included initiatives were those focussing on Black, African diasporic, or African American communities in the North American context. Community-led action, as well as initiatives in primary healthcare care, academic journals, and those broadly focused on racialized communities, were excluded from this review. Synthesis Seventy-five articles were included in this review, suggesting that ABR emerged as a public health priority. Strategies and action plans to address structural ABR were the most common types of initiatives observed (n = 21), followed by programs or interventions (n = 16), budget allocations or investments (n = 8), task forces (n = 7), guidance and recommendations for organizational capacity (n = 8), action-oriented declarations of ABR as a public health crisis (n = 8), and legislation and mandates (n = 7). Initiatives were largely cross-cutting of two or more socioeconomic themes (n = 23), while organizational change was also common (n = 16). Gaps in the current literature include a lack of community participation and outcome measurement for actions identified, which limit institutional accountability to communities of interest. Conclusion This research provides insights on public health accountability to social justice. This research outlines activities in upstream interventions, organizational transformation, and resource allocation in shaping anti-racist change, and require evaluation and input from those whom initiatives are intended to serve.